Evaluation of risk factors can help to predict preterm delivery within 7 days in women hospitalized for threatened preterm labour. (1st October 2016) - Raba, Grzegorz; Kotarski, Jan
Abstract: Objective : The ability to predict birth within 7 days of enrolment in women hospitalized for threatened preterm labour is essential for a proper decision to introduce corticosteroids for the treatment. Method : The study included 622 women hospitalized due threatened preterm labour. Eighteen risk factors were analysed. The predictive value for accumulation of studied risk factors was assessed using receiver operating characteristic (ROC) curve analysis and dimension-based models of assessment methods: (i) forward stepwise selection (conditional), (ii) forward stepwise selection (Wald) and (iii) backward stepwise elimination (conditional). Results : The accumulation of five and above risk factors gives specificity and positive predictive value (PPV) of diagnosis preterm delivery within 7 days of enrolment approaching 100% (99 and 98, respectively). The predictive value for studied risk factors enabled establishing the following order for risk factors significance: (i) cigarette smoking before pregnancy; (ii) low socioeconomic status; (iii) frequent contractions during pregnancy; (iv) bleeding during pregnancy; (v) urinary tract infections. Conclusion : In women hospitalized for threatened preterm labour, the accumulation of five risk factors of preterm delivery predicts preterm delivery within 7 days of enrolment. That makes easier decision to introduce corticosteroids for the treatment.